DINAMIKA PEMBENTUKAN KEBIJAKAN MELALUI METODE DAKWAH PADA KAJIAN KEPEMIMPINAN NABI MUHAMMAD SAW: STUDI LITERATUR - Nurdalipah Hasugian; Abdul Mukti; Zaini Dahlan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2022)
The early Islamic history that was passed by the Prophet Muhammad SAW was really difficult, because he had to deal with the Quraysh tribe who controlled the city of Mecca. The followers of Rasulullah at that time were still very few and the main focus of the prophet's da'wah at that time was to improve monotheism which had turned with the changing times. In general, the da'wah of the Prophet Muhammad SAW has 2 periods, namely the period in Mecca for approximately 13 years, then the period in Medina for less than 10 years. The method used by the prophet in preaching is secretly and openly.Rasulullah SAW provided himself with kindness, piety and sincerity and noble character in guiding mankind so that it aroused sympathy from the people who easily accepted the teachings of Islam. Even so, there are still many from the Quraysh infidels who reject the teachings of the Prophet Muhammad SAW because they consider the teachings of the Prophet Muhammad to be divisive teachings.